Use of intravenous cyclophosphamide in known or suspected, advanced non-specific interstitial pneumonia - Corte, T.J.; Ellis, R.; Renzoni, et al., E.A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: In severe, progressive interstitial lung disease (ILD), specific diagnosis is often difficult, and treatment therefore empirical. An effective, rapidly acting, well-tolerated therapy is desirable. This study reviews the tolerability and efficacy of IV cyclophosphamide in known or suspected non-specific interstitial pneumonia (NSIP) following the introduction of an IV cyclophosphamide protocol. Methods: Records of 54 patients with biopsy-proven (n=7) or suspected NSIP, based on clinico-radiological consensus (n=47), receiving IV cyclophosphamide over 2004-6 were reviewed (excluding systemic sclerosis). Lung-function trends over six months were evaluated, and comparative analysis of paired pulmonary-function before and after the start of therapy was performed. Results: IV cyclophosphamide was well tolerated, with two withdrawals from therapy, and four deaths, not directly related to treatment. IV cyclophosphamide was associated with disease stability at six-months. Despite having severe, progressive disease, patients receiving IV cyclophosphamide had stable lung function at six months. A greater therapeutic response was associated with coexistent HRCT abnormalities indicative of organizing pneumonia. In 22 patients with paired pulmonary-function tests, pulmonary function trends were significantly improved (p=0.03) and change in DLco differed significantly (p